Public Market Information and Venture Capital Investment - Gibbons, Brian (Journal of Financial and Quantitative Analysis, 2023)
I study venture capital firms’ (VCs) use of public market information and how attention to this information relates to private market investment outcomes. I link web traffic to public filings hosted on EDGAR to individual VCs. VCs analyze public information about industry peers before most deals. An increase in industry filing views relates positively to the probability of an exit through acquisition, suggesting that public information helps identify paths to acquisition. The effect is stronger when the VC has less access to private information, especially for low-reputation VCs. Policymakers should consider spillover effects on private markets when setting public disclosure requirements.